Gonad development and blood plasma profile of female bada fish (Rasbora sp.) by giving a combination of the hormones estradiol and spirulina in the feed - Ira Akhdiana; Muhammad Zairin Jr; Gadis Sri Haryani; Muhammad Agus Suprayudi (Jurnal Iktiologi Indonesia, 2021)
This study aimed to evaluate the effect of the combination of estradiol-17β hormone and spirulina in feed on blood plasma biochemistry, histology, and gonad development of female bada fish (Rasbora argyrotaenia). The research method were an experimental study using a completely randomized design with four treatment combinations and four replications, namely without the addition of the estradiol-17β hormone and spirulina (P0), the addition of the estradiol-17β hormone at 7 g kg-1 feed (P1), the addition of spirulina at 30 g kg-1 feed (P2) and the addition of the estradiol-17β hormone at 7 g kg-1 feed and spirulina at 30 g kg-1 feed. Female bada fish (4.22±1.28 g) were kept in an aquarium measuring 100x50x50 cm3 with a density of seven individuals per aquarium. Fish were fed the treatment twice daily, with 3% of the biomass for six weeks. The test parameters were estradiol-17β hormone concentration, egg diameter, blood plasma glucose concentration, blood plasma total cholesterol concentration, and gonadal histology observations. The experimental results showed that the concentration of the estradiol-17β hormone in the body plasma of treatments P1 and P3 was statistically significantly different (P<0.05) compared to treatments P0 and P2. The combination of estradiol-17β hormone and spirulina added to the feed gave not significantly different results (P>0.05) on blood plasma biochemistry and egg diameter of bada fish broodstock. A combination of estradiol-17β hormone and spirulina hormones in the feed resulted in better P1 and P3 treatments with higher plasma concentrations of the estradiol-17β hormone. Observations of gonadal development from histology showed that the bada fish gonads belonged to the asynchronous type. Abstrak Penelitian ini bertujuan untuk mengevaluasi pengaruh pemberian kombinasi hormon estradiol-17β dan spirulina dalam pakan terhadap biokimia plasma darah, histologis dan perkembangan gonad ikan bada (Rasbora argyrotaenia) betina. Metode penelitian adalah penelitian eksperimental menggunakan rancangan acak lengkap dengan empat kombinasi perlakuan dan empat ulangan yaitu tanpa penambahan hormon estradiol-17β dan spirulina (P0), penambahan hormon estradiol-17β sebanyak 7 µg kg-1 pakan (P1), penambahan spirulina sebanyak 30 g kg-1 pakan (P2) dan penambahan hormon estradiol-17β sebanyak 7 µg kg-1 pakan dan spirulina sebanyak 30 g kg-1 pakan. Ikan bada betina (4,22±1,28 g) dipelihara dalam akuarium berukuran 100x50x50 cm3 dengan kepadatan tujuh ekor per akuarium. Ikan diberi pakan perlakuan dua kali sehari, sebanyak 3% dari biomassa selama enam minggu. Parameter pengujian yaitu konsentrasi hormon estradiol-17β, diameter telur, konsentrasi glukosa plasma darah, konsentrasi kolesterol total plasma darah dan pengamatan histologis gonad. Hasil percobaan terlihat konsentrasi hormon estradiol-17β dalam plasma tubuh perlakuan P1 dan P3 secara statistik berbeda nyata (P<0,05) dibandingkan dengan perlakuan P0 dan P2. Pemberian kombinasi hormon estradiol-17β dan spirulina yang ditambahkan pada pakan memberikan hasil yang tidak berbeda nyata (P>0,05) terhadap biokimia plasma darah dan diameter telur ikan bada. Penambahan kombinasi hormon estradiol-17β dan spirulina dalam pakan menghasilkan perlakuan P1 dan P3 lebih baik dengan nilai konsentrasi hormon estradiol-17β pada plasma tubuh lebih tinggi. Pengamatan perkembangan gonad dari histologis menunjukkan bahwa gonad ikan bada termasuk tipe yang asynchronous.